2021
DOI: 10.3390/ijms222010997
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Drosophila melanogaster TRPA1 Isoforms by Citronellal and Menthol

Abstract: Background: The transient receptor potential ankyrin 1 (TRPA1) cation channels function as broadly-tuned sensors of noxious chemicals in many species. Recent studies identified four functional TRPA1 isoforms in Drosophila melanogaster (dTRPA1(A) to (D)), but their responses to non-electrophilic chemicals are yet to be fully characterized. Methods: We determined the behavioral responses of adult flies to the mammalian TRPA1 non-electrophilic activators citronellal and menthol, and characterized the effects of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…In addition to participating in the response to harmful temperature stimuli, dTRPA1 has also been detected in chemical stimuli ( Tracey et al, 2003 ; Im and Galko, 2012 ). Boonen et al (2021) found that wild-type flies avoid citronellal and menthol in olfactory tests, while dTRPA1 mutant flies have reduced this behavior. dTRPA1 channel mediates chemical avoidance in gustatory receptor neurons (GRNs), in which know down of dTRPA1 in GRNs significantly reduced the aversive response to aristolochic acid ( Kim et al, 2010 ).…”
Section: The Role Of Pain-related Genes In Regulating Nociception/painmentioning
confidence: 94%
See 3 more Smart Citations
“…In addition to participating in the response to harmful temperature stimuli, dTRPA1 has also been detected in chemical stimuli ( Tracey et al, 2003 ; Im and Galko, 2012 ). Boonen et al (2021) found that wild-type flies avoid citronellal and menthol in olfactory tests, while dTRPA1 mutant flies have reduced this behavior. dTRPA1 channel mediates chemical avoidance in gustatory receptor neurons (GRNs), in which know down of dTRPA1 in GRNs significantly reduced the aversive response to aristolochic acid ( Kim et al, 2010 ).…”
Section: The Role Of Pain-related Genes In Regulating Nociception/painmentioning
confidence: 94%
“…The Drosophila genome contains genes encoding 13 TRP channels, and encodes four TRPA homologs: dTRPA1 , painless , pyrexia , and water witch ( Fowler and Montell, 2013 ). TRPA channels have been the most widely studied for their roles in temperature-sensing behavior in flies ( Goodman, 2003 ; Xu et al, 2006 ; Neely et al, 2011 ; Bellemer, 2015 ) and also play important roles in chemical and mechanical sensing ( Mandel et al, 2018 ; Boonen et al, 2021 ). TRPA1 has been implicated as a mammal noxious cold receptor, which is activated by extremely cold temperatures (below < 15°C) ( Kwan and Corey, 2009 ).…”
Section: The Role Of Pain-related Genes In Regulating Nociception/painmentioning
confidence: 99%
See 2 more Smart Citations
“…TRPA1 channels have been extensively studied across species and are activated by various natural irritants, such as citronellal, cinnamaldehyde, AITC, aristolochic acid, menthol, cinnamodial, and nepetalactone. These chemicals induce avoidance behaviors in Drosophila melanogaster, Tribolium castaneum, the cotton bollworm (Helicoverpa armigera) and multiple mosquito species (Aedes aegypti, Anopheles gambiae, Anopheles stephensi, and Culex pipiens pallens) (Kang et al, 2010;Kim et al, 2010;Kwon et al, 2010;Du et al, 2015;Wei et al, 2015;Inocente et al, 2018;Li et al, 2019;Boonen et al, 2021;Melo et al, 2021;Shimomura et al, 2022). Therefore, insect TRPA1 activators are promising leads for novel repellents with a broad spectrum.…”
Section: Introductionmentioning
confidence: 99%